Production of two novel antifungal peroxidase isoenzymes from Tabernaemontana catharinensis using a bubble-column bioreactor - Reis-Costa, Leonice dos; Macedo, Jamile M.; Lima, Anderson M.; Souza, Mateus F.; Araújo, Erika C.S.; Marcussi, Silvana; Coppede, Juliana; Pereira, Paulo S.; Lourenço, Miriam V.; Pasotto, Marlei B.; Contiero, Jonas [UNESP]; França, Suzelei C.; et al. (Elsevier, 2025)
Plant peroxidases are enzymes with significant antioxidative properties and catalytic versatility, making them valuable for various applications in biotechnology. However, their commercial use is often constrained by inefficient production methods. In this study, we isolated and characterized two peroxidase isoenzymes, TcPOX-I and TcPOX-II, from Tabernaemontana catharinensis using scalable plant cell culture techniques, offering a sustainable alternative to traditional enzyme production methods. By successfully scaling up cultures from flasks to a 3 L bubble-column bioreactor equipped with optimized aeration, aseptic conditions, and real-time monitoring, we enhanced peroxidase production efficiency. Although biomass in the bioreactor was lower than in flask cultures, peroxidase secretion per unit of mass was higher, demonstrating that the bioreactor conditions favored enzyme production over cell proliferation. TcPOX-I and II were isolated via size-exclusion chromatography, exhibiting molecular masses of approximately 34 kDa and isoelectric points of 6.7 and 6.8, respectively. Amino acid sequencing confirmed high homology with known plant peroxidases, while carbohydrate analysis revealed about 4% carbohydrate content, classifying both as glycoproteins. Notably, their enzymatic activity was unaffected by deglycosylation, suggesting potential for heterologous expression. Both isoenzymes displayed optimal activity at pH 6.5 using guaiacol as the substrate, along with unique thermal stability and metal ion response profiles. These properties suggest promising applications in biosensing, biocatalysis, and environmental remediation. Importantly, TcPOX-I and TcPOX-II exhibited concentration-dependent antifungal activity against Candida albicans and Penicillium sp., highlighting their potential as natural antifungal agents. Overall, this work demonstrates the scalable bioreactor production of two, deglycosylation-tolerant peroxidases from T. catharinensis, paving the way for their exploitation in diverse biotechnological applications.
Keywords: Antifungal activity; Bioreactor; Enzyme; Peroxidase; Plant cell culture; Tabernaemontana catharinensis